Writing Back to the Canon: The Birchbark House as Counter-Narrative to Little House on the Prairie - Marisa da Silva Martins (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
ABSTRACT: This article focuses on two children’s novels: Little House on the Prairie (1932) by Laura Ingalls Wilder, and The Birchbark House (1999) by Louise Erdrich. Both works are set in the nineteenth century, specifically during the westward expansion, and during the forced displacement of Indigenous communities. This article aims to read the two novels as opposing narratives, particularly regarding the ways in which settler-colonialism and Native Americans are represented. Through a postcolonial lens, this article aims to show Louise Erdrich’s novel as a counter-narrative, in which the culture and way of life of the Ojibwe community is put in the foreground, as well as its resistance toward white settlers.